(untitled) (Research, Society and Development, 2020)
Objective: Objective: To describe the experiences of students of the undergraduate course in Collective Health at the Universidade Federal do Rio Grande do Norte (UFRN) during the curricular internship in the teaching-service-community interaction in Primary Care and the promotion of users’ health. Method: Descriptive study, of the experience report type of experiences during the curricular internship in a Primary Care service in the city of Natal, Rio Grande do Norte / RN in the first semester of 2019. Results: From observation and conversation with professionals and users, students were able to outline objectives and plan experiences focused on mental health, medicalization and qualified listening, with the participation of professionals from the unit and guests, in addition to the users of the unit. health of conducting the internship. Conclusions: Experiences experienced during the curricular stage in Primary Care were presented as an important strategy for the strengthening of the teaching-service-community interaction and in the preparation of the student to use the living environment of their professional practice. The moments focused on health promotion were rich and important in the development of the students in the expansion of their perception of the concept of health-disease, comprising this as multifactorial and unique in each person.